Parental leave, childcare and gender equality in the Nordic countries - Ingólfur V. Gíslason; Guðný Björk Eydal (TemaNord ;, 2011)
This book investigates whether pioneering work in the area of gender equality in the Nordic countries has come at the expense of children. It reviews political and policy developments in parental leave and childcare for their impact on child welfare and wellbeing. Topics include: the developmental of the Nordic parental leave system, factors influencing the use of parental leave, day-care schemes, cash-for care at home, the best interests of children, starting age for kindergarten, the best interests of the child and parental labour force participation, freedom of choice and underlying motives, and the role of political parties in policy making.